Standaryzacja tekstowa inwentarzy wiejskich z XVII wieku - Kość, Józef (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
Textual Standardization of Rural Inventories in 17th Century occurred in the process of official language communication during the inspection of royal land manors, which was conducted between 16th and 18th centuries. The repetitiveness and stability of structure of this process of language communication, and the official conceptualization of inventoried stock, as well as the inspectors’ intention to be communicative, shaped the 17th-century standard inventory, which consisted of stable textual components, i.e. official terminology, parallel syntactic structures, initializing and finishing formulae, and composition of text, which conformed to the universal accounting formula used for tax purposes: revenue – cost = income under taxation. The constitutive unit of this structure, which for practical purposes reduced description of listed objects, is a categorizing inventory including groups of people, properties, objects, and sources of income in money and in kind. The 17th-century rural inventory, as a textual pattern embedded in the language consciousness of state officials and reinforced legally by treasury instructions, cumulates the uniform and repetitive forms of official language, and approaches the modern form of inventory, which prefers tabular and form-based approaches.